E-contracts in Nigeria, legal issues, challenges and prospects (2021)
Trade and trading activities in the 21st Century have taken a new trend. Unlike in the early centuries, commercial transactions are now carried out with much ease given the technological advancement. This technological advancement has given rise to what is known as electronic contract (e-contract). This term is sometimes used inter-changeably with e-commerce. Nigeria as a nation is not left out of the aforesaid development, hence Nigerian economic space does not only recognise e-contract but also encourages its growth within the environmental sphere of the available infrastructural facilities. E-Contractor e-Commerce is defined as the practice of buying and selling of goods and Services through online consumer Services on the internet. This usually involves online advertisement, negotiation, contractual agreement, payment (fintech) and delivery of goods and Services. However, this kind of contractual relationship is not without its challenges, particularly in Nigeria which records deficit in the area of Provision of infrastructural facilities and enabling environment (a good example is the erratic supply of electricity and high cost of internet facilities which is an offshoot of the former) constitute hindrances to the growth of e-contract. This paper therefore examines the legal issues, challenges and prospects of e- contract in Nigeria.